2020
DOI: 10.3390/foods9030304
|View full text |Cite
|
Sign up to set email alerts
|

Antiradical Activity of Hydrolysates and Extracts from Mollusk A. broughtonii and Practical Application to the Stabilization of Lipids

Abstract: The antiradical properties of hydrolysates and hydrothermal extracts of bivalve mollusks (Anadara broughtonii) from the Far Eastern Region of Russia and their influence on lipid oxidation in mayonnaise were investigated. The radical binding activity of hydrolysates and extracts of A. broughtonii varies from 55% to 89%. The maximum radical-binding activity was observed for acid hydrolysates. The antiradical efficiency of acid hydrolysates is 35%-41% of the BHT (butylhydroxytoluene) index. The antiradical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Since the generation of free radicals is also related to heating processes, investigation of the effects of antioxidant on the changes in MCPD esters and GE during conventional baking using palm-based shortening is the main focus of this study. Antioxidants used in food applications can extend the fatty food storage time by slowing down the oxidation process [16] For example, butylated hydroxyanisole (BHA) is used in fried food, and the application of two or more antioxidants can act synergistically to maximize the functional properties [17,18]. It is also reported that antioxidant extracts incorporated into the food or food packaging material can hinder the lipid deterioration within a meat product [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Since the generation of free radicals is also related to heating processes, investigation of the effects of antioxidant on the changes in MCPD esters and GE during conventional baking using palm-based shortening is the main focus of this study. Antioxidants used in food applications can extend the fatty food storage time by slowing down the oxidation process [16] For example, butylated hydroxyanisole (BHA) is used in fried food, and the application of two or more antioxidants can act synergistically to maximize the functional properties [17,18]. It is also reported that antioxidant extracts incorporated into the food or food packaging material can hinder the lipid deterioration within a meat product [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Tabakaeva and colleagues studied the antiradical properties of hydrolysates and hydrothermal extracts of bivalve mollusks ( Anadara broughtonii ). They also evaluated their effect on lipid oxidation and lipolysis in mayonnaise [ 5 ]. They studied hydrolysates obtained either by acid or enzymatic hydrolysis and observed that acid hydrolysates were more efficient than enzymatic hydrolysates in preventing oxidation and lipolysis in mayonnaise.…”
mentioning
confidence: 99%